Review on water quality monitoring technologies - Josephine Ong Ning Ting; S. K. Yee (Institute of Advanced Engineering and Science, 2020)
Water quality monitoring is always the prior element to ensure the drinking water is safe to be consumed. A lot of researches have been carried out over the past decades to design and develop a robust and cost-effective water monitoring system. The conventional water monitoring techniques were based on laboratory instruments which is time-consuming and laborious. Furthermore, it is not suitable when the water sampling point is far from the commercial laboratory centres. These limitations were then been solved by the developments of portable testing kits and microwave technique. The microwave techniques such as spectroscopy techniques and microwave sensor approach have improved the water quality monitoring experience which is convenient without sacrificing the measurement accuracy and sensitivity. Its portability enables the on-site measurement at rural areas and thus reduce the transportation and manpower cost. This paper intends to review the water contaminant detection techniques which include standardized drinking water parameter testing and microwave-based in terms of physical, chemical and microbiological parameters. Furthermore, this review also emphasizes the current trend of the water quality testing method in microwave technique. At the end of this paper, a significant advantages and drawbacks of the techniques are summarized, and recommendations are provided for future development in the water quality monitoring.